The Effect of Dividend Policy on Firm Value in the Era of Global Economic Uncertanty - Putri, PA Andiena Nindya; Amalo, Fitriningsih; Amalia, Mekar Meilisa (International Journal of Economics Development Research (IJEDR), 2025)
Global economic uncertainty, heightened by events such as the COVID-19 pandemic, geopolitical tensions, and volatile commodity prices, has reshaped the dynamics between dividend policy and firm value. This article review synthesizes studies published from 2020 onward that investigate how dividend payout decisions influence firm valuation across diverse industries and markets during periods of heightened uncertainty. The review highlights that while traditional dividend theories such as signaling, bird-in-hand, and agency cost hypotheses remain relevant, recent evidence suggests that market reactions to dividend changes have become more sensitive to macroeconomic volatility and investor sentiment. Many firms facing liquidity constraints opted for dividend cuts or suspensions, which often triggered negative short-term valuation effects but supported long-term resilience and investment capacity. Conversely, firms maintaining stable dividends tended to signal financial robustness, mitigating investor anxiety and enhancing firm value despite uncertain conditions. The review also identifies moderating roles of corporate governance, ownership structure, and ESG practices in shaping this relationship. By integrating these findings, the article underscores the importance for managers and policymakers to adapt dividend strategies to evolving global risks, balancing shareholder returns with financial flexibility and sustainable growth objectives.